One problem two issues! Left ventricular systolic and diastolic dysfunction in aortic stenosis - Elahi, Maqsood M. (AME Publishing Company, 2014)
Reports suggested that immediate post-aortic valve replacement (AVR); left ventricular (LV) dysfunction may be an important risk for morbidity and mortality in patients requiring positive inotropic support. Several factors have been identified as significant prognostic factors i.e., LV systolic dysfunction, LV diastolic dysfunction (LV-DD), heart failure and myocardial infarction (MI). Specific to pathophysiological changes associated with AS, markers of systolic LV function (e.g., LVEF) have been extensively studied in management, yet only a few studies have analysed the association between LV-DD and immediate post-operative LV dysfunction This review brings together the current body of evidence on this issue.